Bridging Two Worlds: Colloidal versus Epitaxial Quantum Dots. Issue 6 (17th May 2019) - Bayer, Manfred
Abstract: An overview is given of two distinct classes of semiconductor quantum dots, epitaxial and colloidal structures that have been studied intensely for more than 30 years by now, however, without large interconnection between the two involved research communities. The largely parallel and independent evolution of the two structure classes may be partly related to the origin of colloidal systems from chemistry, while epitaxial quantum dots have been addressed mostly by the physics community. These independent evolutions are somewhat surprising because the interest in optics‐related applications is shared by both communities. Here, a short summary of the development of the two structure classes, the present status of activities, and some perspectives for future developments are presented. Abstract : A short comparison of the development of the research areas of colloidal and epitaxial quantum dots during the last more than 30 years is drawn . The focus of this comparison is on optical studies and optoelectronic applications, highlighting particular strengths of the two classes of quantum dots.